Self-Optimism Psychoeducation and Resilience Patterns among Prison Inmates - Wendy Afuan Fakhri; Lely Ika Mariyati (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Prison inmates face psychological stressors that require strong resilience to adapt and prepare for social reintegration. Specific Background: Psychoeducation focusing on self-optimism is frequently used in correctional settings to support inmates’ mental adjustment, yet outcomes vary. Knowledge Gap: Empirical evidence remains limited regarding how self-optimism psychoeducation relates to changes in inmate resilience, particularly in Indonesian Class I penitentiaries. Aims: This study examined resilience patterns before and after self-optimism psychoeducation among inmates of Class I Surabaya Penitentiary. Results: Using a quasi-experimental one-group pretest–posttest design with 57 participants, statistical analysis showed no significant difference between pretest and posttest resilience scores, although descriptive data indicated shifts across low, moderate, and high resilience categories. Novelty: The study provides context-specific evidence that informational psychoeducation alone may not sufficiently shift resilience levels within a short intervention period. Implications: Findings suggest that psychoeducation should be integrated with sustained support strategies, such as social support and emotional coping approaches, to better address inmates’ psychological needs and rehabilitation goals.